The association between HDL particle concentration and incident metabolic syndrome in the multi-ethnic Dallas Heart Study. (November 2017) - Mani, Preethi; Ren, Hao-Yu; Neeland, Ian J.; McGuire, Darren K.; Ayers, Colby R.; Khera, Amit; Rohatgi, Anand
Abstract: Aims: Metabolic syndrome (MetS) increases atherosclerotic cardiovascular disease (ASCVD) risk. Low HDL cholesterol (HDL-C) is a diagnostic criterion of MetS and a major ASCVD risk factor. HDL particle concentration (HDL-P) associates with incident ASCVD independent of HDL-C, but its association with incident MetS has not been studied. We hypothesized that HDL-P would be inversely associated with incident metabolic syndrome independent of HDL-C and markers of adiposity and insulin resistance. Materials and methods: HDL-P was measured by NMR and visceral fat by MRI in participants of the Dallas Heart Study, a probability-based population sample of adults age 30–65. Participants with prevalent MetS, DM, CVD, and any systemic illlness were excluded. Incident MetS as defined by NCEP ATPIII criteria was determined in all participants after median follow-up period of 7.0 years. Results: Among 1120 participants without DM or MetS at baseline (57% women, 45% Black, mean age 43), 22.8% had incident MetS at follow-up. HDL-P and HDL-C were modestly correlated (r = 0.54, p < 0.0001). In models adjusted for traditional risk factors and MetS risk factors including visceral fat, HS-CRP, triglyceride to HDL-C ratio, and HOMA-IR, the lowest quartile of HDL-P was associated with a 2-fold increased risk of incident MetS (OR 2.1, 95%CI 1.4–3.1; p = 0.0003). Conclusions: Low HDL-P is independently associated with incident MetS after adjustment for traditional risk factors, lipid parameters, adiposity, inflammation, and markers of insulin resistance. Further studies are warranted to validate these findings and elucidate the mechanisms underpinning this association.